Strategies to reduce diarrhea parasitosis and anemia in children under five years high Andean area Peru - Mamani Limachi, Rut; Alberca Lonzoy, Ana; Columbia, Christine Anne; Cajachagua Castro, Mayela (Horizonte Sanitario, 2019)
Objective: To propose an intervention model to reduce cases of diarrhea, parasites and anemia in children under 5 years of age. Method: This work has two parts, one diagnostic and the other is proactive. The first refers to an intervention program, pre-experimental design with pre and post test. 40 children participated. For the experimental group an intervention program was carried out. The effectiveness of the program was identified with the statistical test of T-Student and Mc Nemar, according to the normality test. The purposive part corresponds to the Intervention Model with strategies, based on the philosophical approach of the Dialectical Methodological Conception and the thinking of Enrique Pichón Riviére. Results: In the diagnostic phase, in the case of anemia, the experimental group showed a decrease with a bilateral difference of 0.00 with p <0.05. In the case of intestinal parasitosis and diarrhea, the experimental group showed a decrease with a bilateral difference of 0.001 with p <0.05. The purposed phase corresponds to the intervention model whose pillars are: education and dialogue, behavioral change, empowerment and intersectoral management. Conclusions: The intervention model with preventive strategies, based on the experience of the developed program, will allow to reduce cases of diarrhea, parasitosis and anemia in children under five years. Keywords: Diarrhea; Parasitic diseases; Water pollution; Risk factors; Health education.